2022
DOI: 10.1186/s12888-022-03843-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive brain stimulation combined with psychosocial intervention for depression: a systematic review and meta-analysis

Abstract: Objectives This review investigates the efficacy and safety of non-invasive brain stimulation (NIBS) combined with psychosocial intervention on depressive symptoms. Materials and methods We systematically searched five electronic databases from their inception to June 2021: PubMed, Embase, PsycINFO, Web of Science, and Medline. Randomized or non-randomized clinical trials in which NIBS plus psychosocial intervention was compared to control conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Under this scenario, psychotherapy could gain advantage from NIBS application in terms of enhancing its efficacy and promoting faster and more durable decrements in PTSD symptoms [ 109 , 110 ]. Also, NIBS could benefit from psychotherapy as well, since the neuronal modifications induced by psychotherapeutic interventions would foster the synaptic changes caused by neurostimulation, making them more likely to take place and longer-lasting over time.…”
Section: Discussionmentioning
confidence: 99%
“…Under this scenario, psychotherapy could gain advantage from NIBS application in terms of enhancing its efficacy and promoting faster and more durable decrements in PTSD symptoms [ 109 , 110 ]. Also, NIBS could benefit from psychotherapy as well, since the neuronal modifications induced by psychotherapeutic interventions would foster the synaptic changes caused by neurostimulation, making them more likely to take place and longer-lasting over time.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Psychosocial interventions, which target psychological or social factors instead of biological factors, 19,20 aim to improve various aspects of wellbeing, such as physical, psychological, cognitive, behavioural, and social well-being. 21 These interventions have demonstrated effectiveness in boosting self-esteem, alleviating depressive symptoms, and enhancing QOL for older adults. 22,23 A systematic review and meta-analysis of 69 controlled studies found that psychosocial interventions, including skill training, group support, and social activities, improved positive mental health and QOL while reducing depressive symptoms in older adults without mental disorder diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…Psychosocial interventions, which target psychological or social factors instead of biological factors, 19,20 aim to improve various aspects of well‐being, such as physical, psychological, cognitive, behavioural, and social well‐being 21 . These interventions have demonstrated effectiveness in boosting self‐esteem, alleviating depressive symptoms, and enhancing QOL for older adults 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, dietary capsaicin confers the prevention of depression via regulation of the monoamine transmitter by improving the gut microbiota dysbiosis (12)(13)(14). However, non-invasive brain stimulation (NIBS) is one of the fastest-growing fields in the treatment for major depression (15), and it refers to a set of techniques used to modulate brain activity using non-implantable methods, including electroconvulsive therapy and transcranial magnetic stimulation (TMS) (16,17).…”
Section: Introductionmentioning
confidence: 99%